Any other name eaudiobook - Johnson, Craig (Walt Longmire Mystery, 2014)
"He's like a gun; once you point him and pull the trigger, it's too late to change your mind." Sheriff Walt Longmire is sinking into a high-plains winter discontent when his former boss Lucian Connally asks him to take on a special case: A detective is dead, and Lucian wants to know what drove this by-the-book lawman to take his own life. With the clock ticking on the birth of Walt's first grandchild, he enlists the help of his friend Henry Standing Bear and undersheriff Vic Moretti, and ends up elbow-deep in a cold case involving three missing women. Walt follows the blood trail from a casino in Deadwood to a lodge in the snowy Black Hills of South Dakota to a shady strip club in the neighboring county, uncovering a secret so dark it threatens to claim other lives before the sheriff can serve justice—Wyoming style.